2010
DOI: 10.1111/j.1600-0897.2010.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental Viral Infection Sensitizes to Endotoxin-Induced Pre-Term Labor: A Double Hit Hypothesis

Abstract: Problem-Among pregnant women, acquired viral infections with a concurrent bacterial infection is a detrimental factor associated to poor prognosis. We evaluate the effect of a viral infection that does not lead to pre-term labor on the response to low doses of lipopolysaccharide (LPS). Our objectives were (i) to characterize the effect of a viral infection concurrent with exposure to microbial products on pregnancy outcome and (ii) to characterize the placental and fetal immune responses to the viral sensitiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 31 publications
3
132
0
Order By: Relevance
“…7 Furthermore, cervical HPV infection impairs the physiological protective capacity of the uterine cervix. 30 Studies employing in situ hybridization have detected HPV DNA in non-neoplastic endometrium in 19.6 31 and 60% 32 of biopsies. It is possible that initial infection of the endometrium is facilitated by regular menstrual shedding (akin to wounding), whereas the lack of menstrual shedding, endometrial decidualisation, and immune suppression during pregnancy contributes to HPV persistence and growth.…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, cervical HPV infection impairs the physiological protective capacity of the uterine cervix. 30 Studies employing in situ hybridization have detected HPV DNA in non-neoplastic endometrium in 19.6 31 and 60% 32 of biopsies. It is possible that initial infection of the endometrium is facilitated by regular menstrual shedding (akin to wounding), whereas the lack of menstrual shedding, endometrial decidualisation, and immune suppression during pregnancy contributes to HPV persistence and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Assays were performed according to the manufacturer's instructions as previously described 12, 13, 14. Cartridges containing IL‐6, IP‐10, TNF‐α, and IL‐1β were run alongside the Luminex plates, and data were converted from relative units/RFU to concentration (pg/ml) to directly compare formats.…”
Section: Methodsmentioning
confidence: 99%
“…The maternal immune response can be beneficially or detrimentally affected by pregnancy, depending on the enviare beginning to identify viral infections as potential risk factors for PTB (53,(56)(57)(58). For example, Zuo et al showed that cervical HPV infection was associated with PTB (56), while others determined that genital HSV was also associated with PTB (53,59).…”
Section: Viral Infection and Maternal Healthmentioning
confidence: 99%